2024
DOI: 10.1055/s-0042-1751526
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Multicomponent Synthesis of Heterocycles Using 5-Aminotetrazole

Ramin Javahershenas,
Ata Makarem,
Haibo Mei
et al.

Abstract: The unique reactivity and beneficial features of the 5-aminotetrazole synthon (1H-tetrazol-5-amine) have made it a versatile and effective building block in the synthesis of heterocyclic compounds. In addition, several drugs containing this scaffold with a wide array of biological properties have been already introduced. Heterocyclic structures are the backbone of many biologically active and industrially important compounds. 5-Aminotetrazole is one of the favored synthons used in the preparation of heterocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 131 publications
(197 reference statements)
0
4
0
Order By: Relevance
“…Single-crystal X-ray analyses of the pyrrolidine-fused bis-spirooxindoles unambiguously conrmed their structures and stereochemistries. 182 Mukhopadhyay et al reported a rapid method for the one-pot, chromatography-free synthesis of diversied dihydrospiro [indeno[1,2-b]pyridine]-4,3 0 -indolines (35) or the analogous spiro acenaphthylene-1,4 0 -indeno[1,2-b]pyridines (36). A viable microwave-assisted MCR in minimal aqueous ethanol (1 : 1, v/v) as the green solvent without any metal catalyst was demonstrated by using a mixture of a series of substituted amines (33) and isatins (1) or acenaphthenequinone (1 0 ), malononitrile (17) or acyclic-1,3-diketone (10), and indane-1,3-dione (34) (Scheme 11).…”
Section: Spiroindole Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-crystal X-ray analyses of the pyrrolidine-fused bis-spirooxindoles unambiguously conrmed their structures and stereochemistries. 182 Mukhopadhyay et al reported a rapid method for the one-pot, chromatography-free synthesis of diversied dihydrospiro [indeno[1,2-b]pyridine]-4,3 0 -indolines (35) or the analogous spiro acenaphthylene-1,4 0 -indeno[1,2-b]pyridines (36). A viable microwave-assisted MCR in minimal aqueous ethanol (1 : 1, v/v) as the green solvent without any metal catalyst was demonstrated by using a mixture of a series of substituted amines (33) and isatins (1) or acenaphthenequinone (1 0 ), malononitrile (17) or acyclic-1,3-diketone (10), and indane-1,3-dione (34) (Scheme 11).…”
Section: Spiroindole Frameworkmentioning
confidence: 99%
“…In addition to their rich chemical reactivity and ability to adopt various conformations, spiro heterocycles possess an array of intriguing biological functions due to their unique structural arrangements. [35][36][37][38][39][40] In this review, we report on the recent progress in MCRs 41-46 and summarize a comprehensive overview of the recent advances in the microwave-assisted MCR of spiro heterocycles, highlighting key developments and methodologies that have contributed to the rapid expansion of the technique applied the synthesis of spiro heterocycles. In addition to providing some perspectives for future research, we also outline the benets of this method and some challenges it faces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harnessing this approach, researchers have adeptly accessed an expansive class of biologically active molecules, encompassing pharmaceuticals, agrochemicals, and materials. These substances have promising uses in drug discovery and development since they display a diverse range of pharmacological activities, thus enhancing the synthesis of different heterocyclic frameworks [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%